2015
DOI: 10.3390/jcm4071518
|View full text |Cite
|
Sign up to set email alerts
|

Renal Replacement Therapy: Purifying Efficiency of Automated Peritoneal Dialysis in Diabetic versus Non-Diabetic Patients

Abstract: Background: In order to reduce the cardiovascular risk, morbidity and mortality of peritoneal dialysis (PD), a minimal level of small-solute clearances as well as a sodium and water balance are needed. The peritoneal dialysis solutions used in combination have reduced the complications and allow for a long-time function of the peritoneal membrane, and the preservation of residual renal function (RRF) in patients on peritoneal dialysis (PD) is crucial for the maintenance of life quality and long-term survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…An observational study showed that glycemic control was not associated with changes in RKF during the first year on PD [103]. However, the slope of loss of RKF is more pronounced in patients with diabetes, especially in the first year, diminishing in the following year and, starting from a higher initial urine production, they also experience a greater decrease in it [104].…”
Section: Social: Socialmentioning
confidence: 99%
“…An observational study showed that glycemic control was not associated with changes in RKF during the first year on PD [103]. However, the slope of loss of RKF is more pronounced in patients with diabetes, especially in the first year, diminishing in the following year and, starting from a higher initial urine production, they also experience a greater decrease in it [104].…”
Section: Social: Socialmentioning
confidence: 99%